Molecular Breeding Strategy and Challenges Towards Improvement of Blast Disease Resistance in Rice Crop - Ashkani, Sadegh; Rafii, Mohd Y.; Shabanimofrad, Mahmoodreza; Miah, Gous; Sahebi, Mahbod; Azizi, Parisa; Tanweer, Fatah A.; Akhtar, Mohd Sayeed; Nasehi, Abbas (Frontiers in Plant Science, 2015)
Rice is a staple and most important security food crop consumed by almost half of the world’s population. More rice production is needed due to the rapid population growth in the world. Rice blast caused by the fungus, Magnaporthe oryzae is one of the most destructive diseases of this crop in different part of the world. Breakdown of blast resistance is the major cause of yield instability in several rice growing areas. There is a need to develop strategies providing long-lasting disease resistance against a broad spectrum of pathogens, giving protection for a long time over a broad geographic area, promising for sustainable rice production in the future. So far, molecular breeding approaches involving DNA markers, such as QTL mapping, marker-aided selection, gene pyramiding, allele mining and genetic transformation have been used to develop new resistant rice cultivars. Such techniques now are used as a low-cost, high-throughput alternative to conventional methods allowing rapid introgression of disease resistance genes into susceptible varieties as well as the incorporation of multiple genes into individual lines for more durable blast resistance. The paper briefly reviewed the progress of studies on this aspect to provide the interest information for rice disease resistance breeding. This review includes examples of how advanced molecular method have been used in breeding programs for improve blast resistance. New information and knowledge gained from previous research on the recent strategy and challenges toward improvement of blast disease such as pyramiding disease resistance gene for creating new rice varieties with high resistance against multiple diseases will undoubtedly provide new insights into the rice disease control.